3D meso-scale finite element analysis of FRP-confined concrete - Yang, Jia-Qi; Jin, Yuhang; Feng, Peng; Wang, Zeyuan (Journal of Asian Concrete Federation, 2026)
Fibre-reinforced polymer (FRP)-confined concrete demonstrates strain hardening behaviour under compression. This advantageous mechanical behaviour has been extensively utilized in composite structural design and research. To explore the mechanism of the passive confining effect and the internal damage propagation of concrete, a meso-scale finite element (FE) analysis is performed. In this analysis, concrete is regarded as a three-phase heterogeneous material composed of aggregate, cement matrix, and the interfacial transition zone (ITZ). In this paper, existing meso-scale modelling methods and their key parameters are reviewed. Subsequently, a parametric study is conducted, revealing that the parameter values adopted from existing literature are unsuitable for the passively confined scenario. Consequently, a modification to the key parameters is proposed. Using the proposed modelling approach, FRP-confined concrete cylinders and prisms under axial and eccentric compression are modelled. The results unveil the internal damage evolution and the actual stress distribution within FRP-confined concrete, thus providing a deeper understanding of the mechanism of passive confinement.